Determination of reaction forces at kinematical joints - Do Sanh (Vietnam Journal of Mechanics)
The determination of reaction forces at kinematical joints of mechanism plays an important role in dynamics of machines. In the paper a method of determining the reaction at kinematical joints is presented.